Friction, Lubrication and Wear 2019
DOI: 10.5772/intechopen.85167
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Wear Behavior of Metal Alloys Produced by Laser Powder Bed Fusion (LPBF)

Abstract: Laser powder bed fusion (LPBF) is an additive manufacturing technique for the production of parts with complex geometry, and it is especially appropriate for structural applications in aircraft and automotive industries. Wear is the most important cause of malfunction of mechanical systems. Abrasive wear accounts for 50% of wear in industrial situations, and it is most common in components of machines. LPBF is very attractive due to its extremely high melting and solidification rates that make possible to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This difference can be attributed to grain boundary lubrication and higher hardness for finer grains. The refined grains in SN samples showed a higher wear resistance and lowered COF [76,77].…”
Section: Cof Variations Versus Sliding Distancementioning
confidence: 95%
“…This difference can be attributed to grain boundary lubrication and higher hardness for finer grains. The refined grains in SN samples showed a higher wear resistance and lowered COF [76,77].…”
Section: Cof Variations Versus Sliding Distancementioning
confidence: 95%
“…Larusso [29] concluded that the parts manufactured through laser powder bed fusion present higher wear resistance and a smaller coefficient of friction, under the same dry condition and boundary lubrication, in comparison with parts manufactured through conventional technologies. The main root of this cause is the fine size of the grains and the high hardness.…”
Section: Powder Bed Fusionmentioning
confidence: 99%
“…The tribological properties, particularly wear resistance, are crucial for plastic injection moulds to guarantee efficacy and safety [156], especially when the injected material is reinforced with hard particles, such as glass fibre reinforcements, or when additives like titanium oxide are used [31,52]. The tribological properties are dependent on the microstructure (type of phase(s), shape, and size), porosity, and surface roughness [157].…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…The tribological properties are dependent on the microstructure (type of phase(s), shape, and size), porosity, and surface roughness [157]. Some studies show that the wear resistance of materials processed by LPBF improves when compared to traditional manufacturing processes due to the refined microstructure achieved by the process [156][157][158].…”
Section: Tribological Propertiesmentioning
confidence: 99%